2017
DOI: 10.3390/nu9101087
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Olive Oil Phenolic Compounds on Inflammation in the Prevention and Treatment of Coronary Artery Disease

Abstract: Coronary artery disease (CAD) is responsible for more than 7 million deaths worldwide. In the early stages of the development of atherosclerotic plaques, cardiovascular risk factors stimulate vascular endothelial cells, initiating an inflammatory process, fundamental in the pathogenesis of CAD. The inclusion of potentially cardioprotective foods, such as olive oil, to the diet, may aid in the control of these risk factors, and in the reduction of cytokines and inflammatory markers. The present review aims to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
54
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 145 publications
(167 reference statements)
6
54
0
3
Order By: Relevance
“…In this study, significant differences were observed with respect to inflammatory markers in the aorta tissues among groups treated with HFD and HFD + CEVOO, CaOO or ClOO. Indeed, in HDF fed rats, expression of COX-2, mPGES1, and iNOS was higher than in the standard diet fed rats, and the HFD + CEVOO, CaOO or ClOO groups showed a remarkable decrease of the inflammatory status of rat aorta, while increasing protective vascular markers, in line with other findings [69,70]. No significant alterations were observed for enzymes involved in the control of redox state.…”
Section: Discussionsupporting
confidence: 80%
“…In this study, significant differences were observed with respect to inflammatory markers in the aorta tissues among groups treated with HFD and HFD + CEVOO, CaOO or ClOO. Indeed, in HDF fed rats, expression of COX-2, mPGES1, and iNOS was higher than in the standard diet fed rats, and the HFD + CEVOO, CaOO or ClOO groups showed a remarkable decrease of the inflammatory status of rat aorta, while increasing protective vascular markers, in line with other findings [69,70]. No significant alterations were observed for enzymes involved in the control of redox state.…”
Section: Discussionsupporting
confidence: 80%
“…Human studies have demonstrated that olive oil phenolic compounds exert health-promoting effects and reduce inflammatory markers associated with chronic diseases [1, 2]. In particular, oleuropein, oleocanthal, hydroxytyrosol, and tyrosol are inhibitors of oxidative damage and inflammation in a variety of experimental systems [3].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, olive oil polyphenols exert strong antioxidant activity, reduce vascular endothelial growth factor-induced angiogenic responses, and decrease MMP-9 and -2 expression (30). This may explain the beneficial effects of this food on chronic degenerative diseases, including cardiovascular and autoimmune diseases (28,31,32).…”
Section: Discussionmentioning
confidence: 99%